Juvenile Hormone-Induced Abnormality of Periplaneta americana (L.) - Borah, Nirmali; Hazarika, Lakshmi Kanta (Indian Journal of Entomology, 2023)
Application of juvenile hormone III (JH III) and a JH analogue, methoprene to last instars of Periplaneta americana suppressed adult emergence and caused morphological abnormalities such as twisted wings and asymmetry of appendages resulting in formation of either nymphoids or giant supernumerary nymphs and adultoids. The effects of JH III and methoprene were concentration dependent in inducing aberrations in morphogenetic moult as well as in significantly lowering the body mass (BM) and lipid reserves (LR) in P. americana.